Tilapia cage farming in freshwater reservoir using artificial diets during dry and wet seasons - Baliao, Dan D. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2011)
Netcage culture of Nile tilapia, Oreochromis niloticus L., was conducted in a freshwater reservoir in Dingle, Iloilo, Philippines from February to October 2009 using Test diet (SEAFDEC/AQD) vs. Commercial feed A (Tateh) in the dry season and Test diet vs. Commercial feed B (Hoc Po) in the wet season. Percent crude protein for Test diet, Commercial feed A and Commercial feed B were 34–35%, 27–33% and 25–32%, respectively. Values for crude fat, crude fiber, crude ash and moisture were 6.0–6.5%, 3.5–5.0%, 10–12% and 4–12% for Test diet; 5–7%, 4.0–8.0%, 12% and 12% for Commercial feed A; and 7%, 4%, 12% and 12% for Commercial feed B, respectively. All netcages were stocked with tilapia fingerlings at 15 m-3 with mean initial weight of 1.2 g and 1.3 g during the dry and wet seasons, respectively.